Investigation of the rigidity and sensitivity dependence of neutron monitors for cosmic ray modulation using algorithm-selected Forbush decreases - Okike, O; Nwuzor, O C (Monthly notices of the Royal Astronomical Society, 2020)
We emphasize the need for a careful and rigorous timing of Forbush decreases (FDs) as well as a correct calculation of FD magnitudes in studies related to cosmic ray (CR) modulation. We have employed Fourier and R-based algorithms for FD event selection, timing and magnitude estimation. The large number of Forbush events that have been identified were employed in correlation and regression analyses to investigate the rigidity and sensitivity dependence of neutron monitors (NMs). It was found that there is a significant difference between the number of FDs identified manually and those selected by the automated method. While the minimum number (238) of FDs occurred at Irkutsk NM, the Novosibirsk CR station observed the largest number (386) of Forbush events. However, within the north high-latitude band (39°N ≤ latitude ≤ 90°N), only 29 FDs have been simultaneously identified using the data from some NMs in the region, including Irkutsk and Novosibirsk. The result obtained using a large number of FDs differs significantly from those employing manual identification of Forbush events. We conclude, among other things, that the automation of FD event selection is essential for understanding the dependence of CR modulation on NM rigidity and altitude, as well as on the contribution from terrestrial modulation agents.